2019
DOI: 10.1002/ece3.5042
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and rapid differentiation after secondary contact between the native green anole (Anolis carolinensis) and the introduced green anole (Anolis porcatus)

Abstract: In allopatric species, reproductive isolation evolves through the accumulation of genetic incompatibilities. The degree of divergence required for complete reproductive isolation is highly variable across taxa, which makes the outcome of secondary contact between allopatric species unpredictable. Since before the Pliocene, two species of Anolis lizards, Anolis carolinensis and Anolis porcatus , have been allopatric, yet this period of indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…The situation of A. carolinensis in southern Florida is complicated by the presence of introduced A. porcatus (Powell et al 2016, Krysko et al 2019). Both of these sets of authors state that there are no morphological differences between the native and introduced form and that they interbreed (as confirmed by Wegener et al 2019) In stating that there are no morphological differences between Anolis carolinensis and A. porcatus, Krysko et al (2019) explicitly relied upon the work of Camposano (2011). The latter author showed that A. carolinensis-group anoles in Miami-Dade County in southern Florida cannot be separated into two distinct moieties corresponding to A. carolinensis and A. porcatus.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The situation of A. carolinensis in southern Florida is complicated by the presence of introduced A. porcatus (Powell et al 2016, Krysko et al 2019). Both of these sets of authors state that there are no morphological differences between the native and introduced form and that they interbreed (as confirmed by Wegener et al 2019) In stating that there are no morphological differences between Anolis carolinensis and A. porcatus, Krysko et al (2019) explicitly relied upon the work of Camposano (2011). The latter author showed that A. carolinensis-group anoles in Miami-Dade County in southern Florida cannot be separated into two distinct moieties corresponding to A. carolinensis and A. porcatus.…”
Section: Discussionmentioning
confidence: 97%
“…2). The great morphological variation in Miami-Dade County doubtless results from the introduction of A. porcatus and subsequent interbreeding (Kolbe et al 2007, Wegener et al 2019 with A. carolinensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that only a few reports on anoles hybridization exist (e.g., Gorman & Atkins, 1968;Glor et al, 2004;Kӧhler et al, 2010;Jezcova et al, 2013;Wegener et al, 2019) and even fewer reports on interspecific mating (e.g., Arias, 1985), might be interpreted as evidence of the existence of good reproductive isolating mechanisms, but could also be interpreted as a lack of combined genetic and morphologic investigations. (Schenk et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, moderate admixture can also contribute to colonization success by minimizing deleterious effects of reduced intra-population diversity or by introducing favorable alleles and enhancing evolutionary potential (Keller & Taylor 2010). That introgression between taxa contributes to adaptation and sorting of genes has become increasingly recognized as a major contributor to population divergence and speciation (Abbott et al 2013;Lamichhaney et al 2015;Wegener et al 2019). Based on our genomic analyses and on the migration rates reported here and in Yeh and Price (2004), as well as in the phenotypic studies in Yeh (2004), it seems that several over-wintering birds on the UCSD campus came from populations other than pinosus , and some of these may have remained to breed on campus.…”
Section: Geographic Origin Of the Ucsd Juncosmentioning
confidence: 99%